Responsabilidad social corporativa: qué se hace y qué debe hacerse - Solano, David (Universidad ESAN. ESAN Ediciones, 2005)
Corporate Social Responsibility has caught the attention of the business community worldwide because consumer and capital markets now champion or punish a company for its relationship with its environment. But this approach is still new and has several defects: it’s reactive, excessively focused on mass media, it’s not specialized, it confuses Public Relations with Social Responsibility, etc. This shows not only little knowledge of the basic concepts but also of the main reason underlying any Social Responsibility process: a sustainable improvement in the relationship with the population as a foundation for sustainable development. In order to achieve this it is necessary to have clear objectives, an clear definition of the target audience, and well designed action plans. Only then will we be able to assess the success or failure of our intervention.

La responsabilidad social empresarial o corporativa es uno de los principales temas de interés de los empresarios en el mundo, porque los mercados de consumo y de capitales premian o castigan la relación de las empresas e instituciones con su medio. Sin embargo, en la actualidad este abordaje es aún incipiente y presenta varias incorrecciones: es reactivo, excesivamente mediático, poco especializado y confunde filantropía o relaciones públicas con responsabilidad social. Refleja poco conocimiento no sólo de los conceptos básicos, sino también de la razón de ser de todo el proceso de responsabilidad social: la mejora constante de las relaciones con la población como base para el desarrollo sostenible. Para lograr esta meta es necesario trazar objetivos claros, definir adecuadamente el público objetivo y diseñar planes de acción estructurados y coherentes. Sólo así podremos evaluar el éxito o fracaso de nuestra intervención.
Keywords: Social responsibility; Social marketing; Responsabilidad social; Márketing social; Planning; Planificación; https://purl.org/pe-repo/ocde/ford#5.02.04